Evaluation of predictive factors for conception after saline infusion sonosalpingography - Dalal Ramadhan; MARWA AL-Rasheedy; Luma Alsarraj (Medicinski glasnik, 2026)
Objective: For evaluation of predictive factors of sponataneous conception after saline infused sonosalpingography (SIS). Method: A prospective study was conducted from August 2023 to December 2024 at reproductive medial unit at Mosul/Iraq. 100 women were recruited and categorized in to two groups: pregnant after SIS and non pregnant after SIS , for achievement of conception, the two groups were followed for 6 months duration and their clinical characteristics were compared . Results: The group where polycystic ovary syndrome (PCOS) positive ladies were included show the duration of infertility for positive pregnancy test ladies was ? 2 years in 58% versus 42% > 2 years (p=0.0001),the history of cesarean section(CS) shows significant difference between pregnant and non pregnant (p=0.11). time to get pregnant after Saline -enhanced sonography shows 79% ? 2 months versus 21% > 2 months. the PCOS variable shows significant difference between pregnant women and non (p=0.037),the incidence of pregnancy was 24% markedly higher in first 2 months after doing the SIS equal to 79% , anti-mullerian hormone( AMH) didn’t show significant difference While in the group where PCOS positive ladies were excluded show the duration of infertility for pregnant ladies was ? 2 years in 66.7% versus 33.3% > 2 years (p=0.001),the history of CS shows considerable difference between pregnant and non pregnant (p=0.034). time neded to get pregnant after SIS shows 60% ? 2 months versus 40% > 2 months.,the pregnancy rate was 21.1% and notably higher in first 2 months after excuting hydrosalpingography equall to 60% ,AMH show significant difference in pregnant was 1.5ng/ml versus 1.2 in non Conclusion: The current study declare that SIS has positive effect on spontaneous conception this is must true in first two months after doing the SIS and it encourage considering expectant management for ladies with briefer duration of infertility, good ovarian capacity and less pelvic operation history KEYWORD: Infertility, Saline infusion sonosalpingography,Tubal patency,
Keywords: infertility; salineinfusion sonosalpingography; tubal patency